Chest discomfort in a patient with cancer. Issue 6 (June 2015) - Rabener, Michael J.; Howell, Christopher
<x xml:space="preserve">Abstract</x> ABSTRACT Patients with cancer are at higher risk for venous thromboembolism than patients without cancer due to hypercoagulability associated with malignancy. This article describes a patient with metastatic renal cell carcinoma who had chest pain over several weeks caused by multiple pulmonary emboli.